The Role of Interpersonal Communication in Enhancing Student’s Academic Success and Social Skill at Vocational College, Universitas Diponegoro - Suryana, Mohammed Aden; Permana, Leo Agus (Journal Commedies, 2025)
Interpersonal communication is a cornerstone of social interaction, playing a vital role in building relationships, fostering collaboration, and enhancing both academic and social experiences. This study explores the significance of interpersonal communication among students at the Vocational College of Universitas Diponegoro, focusing on its impact on academic success, social skill development, and the creation of an inclusive campus environment. Effective communication between students and lecturers has been shown to boost learning motivation and academic achievement, while also facilitating collaboration in group projects and research activities. Additionally, interpersonal communication helps students develop essential social skills, such as public speaking, active listening, and empathy, which are crucial for both academic and professional success. However, challenges such as communication anxiety, cultural differences, and the overreliance on social media can hinder effective interaction. Communication anxiety, particularly when interacting with lecturers or peers, can reduce participation in academic activities, while cultural differences may lead to misunderstandings. Social media, although a useful tool for communication, can sometimes diminish the depth of face-to-face interactions. To address these challenges, strategies such as communication training, multicultural education, and the responsible use of technology are recommended. This study employs a qualitative descriptive approach, involving interviews with active students to gather insights into their communication experiences. The findings highlight the importance of fostering effective interpersonal communication to support students' academic and social development, ultimately contributing to a more inclusive and harmonious campus environment. The research underscores the need for targeted communication programs and activities to enhance students' interpersonal skills and address the challenges they face in a diverse academic setting.